CURRENT SITUATION AND SOLUTIONS TO PROTECT VIETNAM'S POLITICAL SYSTEM AGAINST THE PLOTS OF HOSTILE AND REACTIONARY FORCES - Lê Hoàng, Kiệt (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2022)
The current global political landscape is very complex due to the impacts of the Russia-Ukraine conflict on the international, regional, and domestic politics of Vietnam. Hostile and reactionary forces inside and outside of Vietnam have taken advantage of this complex situation to carry out insidious plots and distort the leadership policies of the Vietnamese government, with the aim of changing political decisions and breaking the non-alignment policy. The paper will clarify some of the sinister schemes being carried out in Vietnam by these hostile forces, as well as historical lessons on the disastrous consequences caused by hostile and reactionary forces on the political systems of the Soviet Union and Ukraine. Research results show that hostile forces are carrying out malicious tactics and schemes through several demands to overthrow and sabotage Vietnam’s political system. Accordingly, the paper proposes several basic solutions to strengthen the struggle against wrongful and hostile viewpoints, and protect the leadership policies of the Vietnamese government in the new period.